Variability of Erythropoietin response to sleeping at simulated altitude: A cycling case study - Garvican, L. A.; Martin, D. T.; Clark, S. A.; Schmidt, W. F.; Gore, C. J. (International Journal of Sports Physiology and Performance, 2007)
Our results indicate that the sEPO response of an individual athlete to simulated altitude is not consistent, although the exact reason for the observed variation cannot be elucidated. In addition to providing an adequate dose of hypoxia (>2200 m for >12 h/d for >21 days),1 the training history and state in which an athlete presents before altitude exposure might need to be considered to maximize any possible hematological benefits of living high and training low. Further research on larger samples of athletes is required to clarify the reproducibility of the sEPO response of elite athletes to simulated altitude and the importance of elevated sEPO on subsequent performance changes when following the live high:train low approach to altitude training.